PENGARUH PEMBIAYAAN MUSYARAKAH DAN MURABAHAH TERHADAP TINGKAT PROFITABILITAS PADA PT. BANK BUKOPIN SYARIAH PERIODE 2008 – 2017 - GIVI EFGIVIA; MUFID HABIB MUSTOFA; RESTINI SAWIDIA (Institut Bisnis Muhammadiyah Bekasi, 2020)
This thesis aiming is to determinate in how much influence Musyarakah and Murabahah agreement in Islamic bank financing against the profitability of Islamic bank. This thesis used PT Bank Bukopin Syariah Tbk profitability period 2008-2017. Data from the financial statement is taken from the publication of the report issue from the website of the bank and Indonesian financial official website (OJK). Mechanical of data management is using multiple linear and data description, while proving the hypothesis parsial